Sex and β-Endorphin Influence the Effects of Ethanol on Limbic Gabra2 Expression in a Mouse Binge Drinking Model - Rhinehart, Erin M.; Nentwig, Todd B.; Wilson, Diane E.; Leonard, Kiarah T.; Chaney, Bernie N.; Grisel, Judith E. (Frontiers in Genetics, 2018)
Binge drinking is a widespread problem linked to increased risk for alcohol-related complications, including development of alcohol use disorders. In the last decade, binge drinking has increased significantly, specifically in women. Clinically, sexually dimorphic effects of alcohol are well-characterized, however, the underlying mechanisms for these dimorphisms in the physiological and behavioral effects of alcohol are poorly understood. Among its many effects, alcohol consumption reduces anxiety via the inhibitory neurotransmitter GABA, most likely acting upon receptors containing the α-2 subunit (Gabra2). Previous research from our laboratory indicates that female mice lacking the endogenous opioid peptide β-endorphin (βE) have an overactive stress axis and enhanced anxiety-like phenotype, coupled with increased binge-like alcohol consumption. Because βE works via GABA signaling to reduce anxiety, we sought to determine whether sexually dimorphic binge drinking behavior in βE deficient mice is coupled with differences in CNS Gabra2 expression. To test this hypothesis, we used βE knock-out mice in a “drinking in the dark” model where adult male and female C57BL/6J controls (βE +/+) and βE deficient (βE -/-; B6.129S2-Pomctm1Low/J) mice were provided with one bottle of 20% ethanol (EtOH) and one of water (EtOH drinkers) or two bottles of water (water drinkers) 3 h into the dark cycle for four consecutive days. Following a binge test on day 4, limbic tissue was collected and frozen for subsequent qRT-PCR analysis of Gabra2 mRNA expression. Water-drinking βE +/+ females expressed more Gabra2 in central nucleus of the amygdala and the bed nucleus of the stria terminalis than males, but this sex difference was absent in the βE -/- mice. Genotype alone had no effect on alcohol consumption or drug-induced increase in Gabra2 expression. In contrast, βE expression had bi-directional effects in females: in wildtypes, Gabra2 mRNA was reduced by binge EtOH consumption, while EtOH increased expression in βE -/- females to levels commensurate with drug-naïve βE +/+ females. These results support the contention that βE plays a role in sexually dimorphic binge-like EtOH consumption, perhaps through differential expression of GABAA α2 subunits in limbic structures known to play key roles in the regulation of stress and anxiety.